Kinetic Model of Biodiesel Processing Using Ultrasound - Bambang Susilo (Jurnal Keteknikan Pertanian, 2009)
Ultrasound is predicted to be able to accelerate the chemical reaction, to increase the conversion of plant oil into biodiesel, and to decrease the need of catalyst and energy input. The application of ultrasound for processing of biodiesel and the mathematical model were conducted in this research. The result of the experiments showed that the ultrasound increased reaction rate and the conversion of palm oil into biodiesel up to 100%. It was better than the process with mechanical stirrer that the conversion was just 96%. The duration to complete the process using ultrasound was 1 minute. It was 30 to 120 times faster than that withmechanical stirrer. Ultrasound transforms mechanical energy into inner energy of the fluids and causes an increasing of temperature. Simultaneously, natural mixing process undergo because of acoustic circulation. Simulation with experiment data showed that the acceleration of transesterification with ultrasound was affected not only by natural mixing and increasing temperature. The cavitation, surface tension of micro bubble, and hot spot accelerate chemical reaction. In fact, transesterification of palm oil with ultrasound still needs catalyst. It needs only about 20% of catalyst compared to the process with mechanical stirrer.Keywords : Biodiesel, transesterification, mathematical modeling, ultrasoundDiterima: 16 September 2008; Disetujui: 10 Pebruari 2009